Survey of lesbian, gay, bisexual, and transgender people's experiences of mental health services in Ireland. (8th March 2013) - McCann, Edward; Sharek, Danika
Abstract Very little is known about the experiences of lesbian, gay, bisexual, and transgender (LGBT) people in relation to mental health services. Therefore, the overall aim of the current research was to explore LGBT people's experiences of mental health service provision in Ireland. The objectives were to identify barriers and opportunities, to highlight service gaps, and to identify good practice in addressing the mental health and well‐being of LGBT people. A mixed methods research design using quantitative and qualitative approaches was deployed. A multipronged sampling strategy was used and 125 respondents responded to the questionnaire. A subset of phase 1 (n = 20) were interviewed in the qualitative phase. Quantitative data was analyzed using descriptive statistics. Qualitative data were analyzed thematically. The sample consisted of LGBT people (n = 125) over 18 years of age living in Ireland. Over three‐quarters (77%) had received a psychiatric diagnosis. Findings include that whilst 63% of respondents were able to be 'out' to practitioners, 64% felt that mental health professionals lacked knowledge about LGBT issues and 43% felt practitioners were unresponsive to their needs. Finally, respondent recommendations about how mental health services may be more responsive to LGBT people's needs are presented.